Recent works on microbes and infections in China selected from the Journal of microbes and infections (China) - Wen, Yu-Mei (World Scientific, 2010)
Microbial infections have been and continue to be a major threat to public health. China has a huge population, among which, microbial infections are of great concern. The Journal of Microbes and Infection, a nationwide journal in China with over 4000 subscriptions, publishes original research articles on microbes and infections in the Chinese language. This book contains selected research articles published in this journal from 2006 to 2007 that have been translated into English, and offers a glimpse of a broad range of microbial infections including the clinical and epidemiological aspects of various viral infections, current status of bacterial infections in hospitals, and severe cases of fungal infections. This book provides a rare opportunity for scientists and physicians abroad to see the completely original research data, rather than just the abstract, based on studies conducted in modern China. Articles on molecular biological and bioinformatic studies are also included. An overview of the recent research trend in medical microbiology and infectious diseases in China will be presented as well. Scientists and physicians working in the fields of virology, microbiology, immunology, epidemiology, vaccinology, and infectious diseases will find the articles in this book fascinating and relevant to their own research and practice.